2011
DOI: 10.1002/jrs.2763
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of Mg‐bearing sodosilicate glasses by Raman spectroscopy

Abstract: The presence of magnesium in glasses of geological, medical, and technological interests influences their physicochemical and durability properties. However, the understanding of the role of magnesium is dependent on the combined knowledge of the structural environment of magnesium in the glass or melt and of the silicate network connectivity of the studied systems. In this article, we present a Raman spectroscopic study of the network connectivity of 10 ternary silicate glasses in the system Na 2 O-MgO-SiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 58 publications
(92 reference statements)
5
31
0
Order By: Relevance
“…The bands appearing in the range 200–850 cm −1 are assigned to Si–O–Si bending of Si against tetrahedral cage with slight displacement of oxygen . Bands at 495 cm −1 (485 cm −1 in this study) and 435 cm −1 are assigned to SiO 4 tetrahedra associated with one bridging oxygen, while the one at 530 cm −1 is due to SiO 4 tetrahedra associated with non‐bridging oxygen . Published data from borosilicate glasses suggest that peaks observed around 950, 1075, and 1120 cm −1 are due to Q 4 Si–O stretching, Q 3 Si‐O − Na + stretching, and to Q 2 Si–O − Na + , respectively .…”
Section: Resultssupporting
confidence: 48%
“…The bands appearing in the range 200–850 cm −1 are assigned to Si–O–Si bending of Si against tetrahedral cage with slight displacement of oxygen . Bands at 495 cm −1 (485 cm −1 in this study) and 435 cm −1 are assigned to SiO 4 tetrahedra associated with one bridging oxygen, while the one at 530 cm −1 is due to SiO 4 tetrahedra associated with non‐bridging oxygen . Published data from borosilicate glasses suggest that peaks observed around 950, 1075, and 1120 cm −1 are due to Q 4 Si–O stretching, Q 3 Si‐O − Na + stretching, and to Q 2 Si–O − Na + , respectively .…”
Section: Resultssupporting
confidence: 48%
“…Hence, we attributed Q 4 at 1,080 cm −1 , Q Si─O─Si at~1,020 cm −1 , Q 3 at~950 cm −1 , and Q 2 at~880 cm −1 . The Q Si─O─Si corresponds to the vibration of the interconnected oxygen between two tetrahedral Q n units as stated in previous studies, [86,87] although Trcera et al [88] assigned it to Q 3 species. Considering the work of Micoulaut et al [89] and Mysen, [90] and the low NBO/T of our glasses (i.e., <1), Q 1 species cannot be present.…”
Section: Evolution Of the Silicate Network Signature As A Function mentioning
confidence: 75%
“…Another difference in the spectra is that in the spectrum of the Mapungubwe Oblate two peaks (or shoulders) can be distinguished around 952 and 987 cm À1 , while in the spectrum of the typical K2 bead only one peak at 990 cm À1 is observed. It has been shown that the presence of magnesium in glasses give rise to an extra peak in the Raman spectrum in this region e the exact position dependent on the composition of the glass (Trcera et al, 2011).…”
Section: K2 Beads and Mapungubwe Oblatesmentioning
confidence: 98%